SOCIAL COMMENTARY IN A FAIRY SONG POEM BY WILLIAM SHAKESPEARE: A STRUCTURALISM STUDY - Tasya Komariah Hrp; Bima Prana Chitra; Hidayati, Hidayati (Pusat Riset dan Inovasi Nasional, 2022)
Social commentary is one aspect related to society in seeing a phenomenon that occurs. The researcher see a phenomenon that occurs in a community environment and is represented by poem. Where poem used figurative language to beautify writing. The object in this research is a poem by William Shakespeare entitled A Fairy Song. This research aims to explain the figurative language contained in A Fairy Song and also to analyze the social comments are found in A Fairy Song. This research used the structuralism theory proposed by Strauss, Wellek and Warren. The sociological literary criticism proposed by Marx and Lukacs. The methodology that used in this research is qualitative method approach with the phenomenological approach by Husserl. There are five figurative language contained in A Fairy Song poem such as alliteration, hyperbole, simile, metaphor and personification. The figurative language here is also used as a social commentary which generates criticism of this poem. Social comments are found because of the words that use figurative language to interpret a meaning. The researcher found the social comments from the used of figurative language such as injustice, discrimination and exploitation.